EVALUATION OF THE CONDITION DEHYDROGENASE CYCLE OF TRICARBOXYLIC ACIDS WHILE ALLOTRANSPLANTING FETAL TISSUE MUSCLE TO RATS - А.А. Yanchukova; S.А. Petrov (European Scientific Journal, ESJ, 2014)
The purpose of our research was to study dehydrogenase CAC (citric acid cycle) activity at allotransplantation of embryonic muscular tissue and operation without replanting. For this purpose, the following enzymes were investigated: piruvate degidrogenase, α- ketoglutarate dehydrogenase, suktsinatdegidrogenase, laktatdegidrogenase, malatdegidrogenase, izotsitratdegidrogenase. So, allotransplantation leads to activation of oxidizing processes in the investigated muscular tissue of an adult individual.